Keluarga Sakinah dalam Perspektif Ulama Tafsir: Studi Terhadap Rumah Tangga Nabi Adam - Agus Miswanto (Universitas Muhammadiyah Magelang, 2019)
The large number of divorces that occur in Indonesia is due to the failure of the establishment of a Sakinah family so that it is a very fundamental case in Islamic law. Therefore, the purpose of this study is to reveal the values ​​of the sakinah family placed by the Prophet Adam and Eve. This study uses a descriptive literature study using content analysis methods and comparative approaches. QS. Al-Baqarah verses 35-37 become the main object with the focus of the study on four interpretations, namely al-Baghawi, Ibn Kathir, al-Alusi, and al-Maraghi. This research found that 1) family life is a nature from the time of Azali; 2) sakinah family can be realized with equality in a love relationship, fulfillment of basic household needs, obedience to sharia rules; 3) sakinah life can be damaged due to violations of Sharia rules and third party intervention; and 4) the destruction of sakinah life can be fixed with each party having an awareness of the mistakes that have been made and then repenting to Allah SWT